SOSIALISASI TENTANG PENINGKATAN PENGETAHUAN HAK KEKAYAAN INTELEKTUAL KOMUNAL BAGI MASYARAKAT DESA OELOMIN, KECAMATAN NEKAMESE KABUPATEN KUPANG - Bire, Chatryen M Dju; Jacob, Yossie Maria Yulianti; Nubatonis, Orpa Juliana; Kaesmetan, Rini Marselin; Nunuhitu, Tiara G (Universitas Mataram, 2024)
People tend not to be interested in taking economic benefits from communal intellectual property due to lack of knowledge. The lack of awareness about the importance of intellectual work assets has led to rampant cases of violations of communal intellectual property. This is the point of awakening awareness of increasing knowledge of intellectual property rights of communal communities. Starting from the above conditions, this community service aims to explain about increasing knowledge of intellectual property rights for the community of Oelomin Village, Nekamese District, Kupang Regency. The solution offered in this community service is to explain intellectual property rights. The method used is through socialization of material delivery and question and answer discussions directly with the local community. The results of the activity show that the socialization given to the local community can increase the understanding and knowledge of the Oelomin Village community related to communal intellectual property rights, this can be seen from the high enthusiasm of the community during the question and answer discussion. Seeing these conditions, it is necessary to do more socialization to the community in order to further deepen and strengthen the understanding of the community related to communal intellectual property rights.